EXPERIENCE OF NOTHINGNESS: A FORM OF HUMANISTIC RELIGIOUS EXPERIENCE - Raymond, Menye (Journal of Dharma, 1989)
The "Experience of Nothingness" in human context is both frightening and fascinating. It is frightening because for many Westerners the idea of Nothingness suggests the notion of chaos, non-reality, or the opposite of anything positive, everything leading to despair and anguish ; it is more or less akin to Nihi/um and the atheistic philosophy of Heidegger or Sartre is the by-word of that position. In trying to understand the same notion in the thought and life of any Eastern people where Buddhism is a cultural force, we will soon discover that it is an invitation to transcendence, ’Absolute’ or fulness of Reality as held by the Buddhist thinker Nagarjuna. When we go through the history of philosophy, we see how men of all ages have almost in the same sweeping vein dealt with some metaphysical problems such as Being and Non-Being. Man wants to know the Real. In all his endeavours to comprehend Reality, Man himself is in the centre of the eternal quest.